2013
DOI: 10.1017/s0022215113000455
|View full text |Cite
|
Sign up to set email alerts
|

Management of incidental and non-incidental papillary thyroid microcarcinoma

Abstract: Papillary thyroid microcarcinomas present both incidentally and non-incidentally, with equal prevalence. Non-incidental tumours not infrequently present with cervical lymph node disease. The patient outcome is generally excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
3
14
0
6
Order By: Relevance
“…Because we did not biopsy all small nodules with suspicious US features, we had detected fewer nonincidental TMC than the Ha et al reported. In the study of Elliott et al, supporting our results, ITMC was half of all TMC . Vasileiadis et al suspected clinically only 81 of 339 patients with TMC .…”
Section: Discussionsupporting
confidence: 86%
“…Because we did not biopsy all small nodules with suspicious US features, we had detected fewer nonincidental TMC than the Ha et al reported. In the study of Elliott et al, supporting our results, ITMC was half of all TMC . Vasileiadis et al suspected clinically only 81 of 339 patients with TMC .…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of thyroid cancer (TC) is rising (1). In Poland in 2000, the number of new cases of this malignancy amounted to 1,457 individuals, while in 2010, this number was 2,192 individuals (1,808 women and 384 men).…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization, TMC is defined as TC measuring ≤10 mm at its greatest dimension (1). The clinical and pathological significance of TMC is widely debated.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of thyroid cancer (TC) is rising. 6 Papillary thyroid carcinoma (PTC) is the most common thyroid cancer, it presents relatively as a low-grade malignancy with good prognosis, and a 10-year survival rate of over 90%. However, the clinical behaviors of this cancer are complex.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization, TMC is defined as TC measuring ≤10mm at its greatest dimension. 6 The clinical and pathological significance of TMC is widely debated. This supports the hypothesis that the incidence of TC depends on the geographical region.…”
Section: Introductionmentioning
confidence: 99%